Utilization of Potato Protein Recovered from Wastewater of Potato Starch Factory as Cattle Feed* - Masayuki Takeguchi; Fumihiko Hasumi; Masatsugu Mayanagi; Masaaki Satou (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
A large amount of wastewater is discharged from potato starch factories in Hokkaido, Japan. The wastewater contains residual potato constituents such as protein, which are named potato fruit juice (PFJ). A powerful stench is generated from PFJ by anaerobic fermentation. In this study, the isoelectric precipitation technique was applied to recover the potato protein from PFJ. Protein recovery from PFJ by acid isoelectric precipitation at pH 3.0 or less reached 80%. PFJ post-protein recovery at pH 3.0 does not produce a powerful stench. Potato protein recovered from PFJ by acid treatment is a useful feed resource. The PFJ in potato starch factory is a potentially promising resource for the production of potato protein. Wastewater from potato starch factories does not have to be waste or a source of powerful stench, it can be a valuable resource.